Student and Tutor Perceptions of the Pedagogical Potential and Challenges of Design Jury as an Assessment Method - Yorgancıoğlu, Derya; Tunalı, Sevinç; ÇETİNEL, MELTEM (Sage Publications Ltd., 2022)
This article examines the pedagogical potential and challenges of the design jury as an assessment method from the perceptions of the tutor/jury member and the design students. It aims to gain an understanding of the factors that create opportunities for, and barriers to, the promotion of learning in the design jury. It inquires the possible contributions of the jury into formative evaluation processes in design education. The results show that (1) the communication modalities, and (2) the evaluation criteria influence the way tutors and students perceive design jury as a pedagogical method. While the hierarchy between the jury member and the student creates a barrier to constructive feedback, a balance between formative and summative evaluations is essential in the design jury. Transparency of evaluation criteria decreases design students' concern for grade. The design jury could also serve for formative evaluation. A student-centred approach to design jury engenders experiences of deep learning.
Keywords: Educational Assessment; Evaluation Methods; Formative Evaluation; Student Evaluation; Design Education; Design Assessment; Design Jury